Numerical sensitivity analysis of TRIP-parameter K on weld residual stresses for steel S355J2+ N. Issue 2 (1st February 2016) - Neubert, Sebastian; Pittner, Andreas; Rethmeier, Michael
ABSTRACT: A combined experimental numerical approach is applied for sensitivity analysis of the transformation induced plasticity (TRIP)-parameter K on weld residual stresses for welding of structural steel of grade S355J2+ N. K was determined experimentally using the Gleeble 3500 facility. A thermomechanical FE model of the real welding process was experimentally validated against temperature field and X-ray stress measurements. Within sensitivity analyses K was varied by several orders of magnitude and the influence on the calculated residual stresses is evaluated by performing corresponding FEA. The correct order of magnitude is sufficient to reproduce the residual stresses qualitatively and quantitatively.